The residential satisfaction of the low-cost housing in The New Second-Tier City of Jiangsu Province, China / Xi Wenjia - Xi, Wenjia (2018)
The residential satisfaction was not only to tell how the current living situation was like, but also to tell from which facets the municipal governments should enhance to improve their expectations of buying homeownerships. However, the current planning of low-cost housing development which was produced in line with the executive form of ‘from top to down’ was not able to achieve what real needs were from the low-income group. There have been very few studies of low-income group’s residential satisfactions with low-cost housing in China. And no study has been done with the relationship between residential satisfaction and four residential components consisting of housing unit characteristics, housing unit supporting services, housing estate supporting facilities, and neighbourhood characteristics plus individual and household’s socio-economic characteristics particularly in the latest second-tier city in Jiangsu province. On the basis of the research background, the unresolved critical questions that must be answered were: what are the levels of satisfactions with residential environment between three phases of low-cost housing projects in Xuzhou city and how to improve dwellers’ residential satisfactions? The aim of this research work was to find out and compare the determinants, and to explore those determinants in order to enhance residential satisfactions of Xuzhou’s low-cost houses. An explanatory sequential mixed mode method design was used, and it involved collecting quantitative data first and then explaining the quantitative results with in-depth qualitative data. In the first, quantitative part, the structured questionnaires data were collected from 86, 95, and 80 participants of Xuzhou’s three phases of low-cost houses to assess their residential satisfactions and found out 14 determinants of 1st phase, 12 key predictors of 2nd phase, and 13 mostly significant variables of 3rd phase. The second, qualitative part was conducted as a follow-up to help explain quantitative results that low-cost housing residents wanted a good social environment and neighbourhood facilities by improving satisfactions of community relationship, resident’s workplace, nearest school and bus/taxi station. Moreover, increasing satisfactions of parking facilities, lighting, children’s playground, and fitness equipment could improve residents’ aspirations of good layout and good maintenance for public facilities. Furthermore, the bad conditions of staircases, corridor, garbage disposal, and lighting brought residents’ aspirations of good maintenance for housing units. The bad ventilation and lighting in the bedroom and toilet made residents ask for good structure designs for housing units. In short, those residents finally wanted their houses to be enhanced according to the standard of commodity housing in order to improve their social economic status in China. Accordingly, the residents’ current living environment was needed to improve by way of public participation to promote their residential satisfactions based upon the cooperation amongst their own, property companies, and local governments.